Description of the nest, eggs, and nestling of Rufous-bellied Bush-Tyrants ( Myiotheretes fuscorufus ) (2015)
The Myiotheretes bush-tyrants are a small clade of Neotropical flycatchers (family: Tyrannidae) localized to narrow elevational strips in the Andes Mountains. Here, we describe the first reported nest of Rufous-bellied Bush-Tyrants (Myiotheretes fuscorufus). It was a large cup nest lined with Usnea lichen and elevated on a sheltered rock ledge behind a flowering Puya bromeliad at 2,985 m asl in the buffer zone of Manu National Park, Peru. We provide a near-complete history of the nest from eggs through fledging, and compare data with previous nesting reports for other Myiotheretes species.